Penerapan Six Sigma dalam Pengendalian Asam Lemak Bebas Optimal Crude Palm Oil - Wirda Novarika AK; Yustiar Gunawan (Jurnal Teknik Ibnusina, 2026)
Maintaining consistent quality of crude palm oil (CPO) remains a significant challenge in palm oil mills, particularly due to fluctuations in Free Fatty Acid (FFA) levels that influence product value and processing efficiency. This study evaluates process capability and proposes quality improvement strategies at PT Perkebunan Nusantara IV PKS Bah Jambi using the Six Sigma DMAIC framework. Production quality data were analyzed through control charts, regression analysis, fishbone diagrams, and Failure Mode and Effect Analysis (FMEA). Initial measurement revealed that the average FFA level exceeded premium standards with a sigma level below two, indicating limited process capability. The findings highlight Fresh Fruit Bunch resting time and overripe fruit as a critical factor affecting quality deviation. Improvement strategies emphasize reducing waiting time and stabilizing sterilization parameters. The study demonstrates that a structured Six Sigma approach can effectively minimize process variability while enhancing operational performance in palm oil processing industries.